Graphic means : A History of Graphic Design Production
Rhatigan, Dan ; Romano, Frank ; Brainerd, Paul ; Gable, Gene ; Garland, Ken ; Shaughessy, Adrian ; Tenazas, Lucille ; Strizver, Ilene ; Craig, James ; Cutsforth, Cede ; Graham, Walter ; Erceg, Joe ; de Bartolo, Carolina ; Heller, Steven ; Chantry, Art ; Huerta, Gerard ; Rambow, Gunter ; Lupton, Ellen ; Garrett, Malcolm ; Farey, Dave ; Brignall, Colin ; Greiman, April ; Brooks, Lou ; Swifty ; Frere-Jones, Tobias ; Berger, Joshua ; Stein, Bernard ; etc.
film